Patterns of abuse and routes of administration for immediate‐release hydrocodone combination products. Issue 9 (3rd August 2017) - Cassidy, Theresa A.; Oyedele, Natasha; Mickle, Travis C.; Guenther, Sven; Budman, Simon H.
Abstract: Purpose: Prescriptions for hydrocodone immediate‐release (IR) combination products have recently decreased, yet they represent the majority of opioid prescriptions dispensed and are commonly abused analgesics among both adults and adolescents. Little data exist to understand the contribution of IR products to the problem of prescription opioid abuse. This study aimed to better understand abuse patterns for hydrocodone IR combination products among adult and adolescent substance abusers. Methods: This cross‐sectional study examines abuse prevalence (including abuse adjusted for prescription volume and morphine milligram equivalents) and abuse characteristics for hydrocodone IR combination products and other prescription opioids among separate samples of adults and adolescents assessed for substance abuse problems or entering treatment from January 2012 through June 2015. Results: Results indicate higher abuse for hydrocodone IR combination products than other opioid categories per 100 assessments but lower per prescriptions dispensed. Hydrocodone IR combination products had similar abuse prevalence to all extended‐release and long‐acting opioids when considering abuse measured per morphine milligram equivalents dispensed. An upward trend in hydrocodone IR combination product abuse was observed among adult substance abusers comparing the period prior to and after Drug Enforcement Administration rescheduling of these products in October 2014. Most individuals reported oral abuse of hydrocodone IR combination products, but snorting, reported by 23% of hydrocodone IR combination product abusers, also appears to be a route of abuse that may have public health relevance. Conclusions: Given their high prescription volume, hydrocodone IR combination products, even at a relatively low prevalence of abuse, may contribute substantially to the overall problem of prescription opioid abuse. Additional public health interventions, including development of abuse‐deterrent formulations for these types of opioid products may aid in reducing their abuse.